Pemberdayaan Kader Kesehatan dalam Deteksi Dini Stroke melalui Penerapan Siriraj Stroke Score (SSS) dan Allen Stroke Score (ASS) di Desa Sungai Alat, Kecamatan Astambul - Annalia Wardhani; Insana Maria; Fir’ad Nugraha; Zahara Noor Fadhilla; Winda Sari (Institut Kesehatan Suaka Insan, 2026)
Stroke is a primary cause of mortality and disability, significantly impacting Indonesia's healthcare burden. Delays in symptom recognition often stem from low public awareness, necessitating community-based early detection. Community Health Workers (CHWs) play a strategic role in initial screening and accelerating stroke referrals. This study aims to enhance CHW capacity in early stroke detection using the Siriraj Stroke Score (SSS) and Allen Stroke Score (ASS) in Sungai Alat Village, Astambul District. A comparative descriptive design with an observational approach was employed, involving 10 CHWs. The intervention included education, practical training on SSS and ASS application, case simulations, and skill evaluations focusing on classification accuracy, assessment duration, and diagnostic precision. All participants (100%) consistently applied both methods with identical classifications. Assessment durations ranged from 10–20 minutes, with diagnostic determination achieved within 15–40 minutes. Education and hands-on training effectively improve CHW competence in community-level stroke detection, facilitating timely and accurate case referrals.